Feminist Approaches to Gender Equity in Perú: The Roles of Conflict, Militancy, and Pluralism in Feminist Activism - Grabe, Shelly (Frontiers in Psychology, 2022)
For the past several decades, coordinated efforts from within the women’s social movement in Perú have led to ground breaking legislation surrounding gender equity - for example the National Gender Equality Policy of 2019 and the Gender Parity Law of 2020. These institutionalized policy changes mark milestones on the path to gender equity, certainly in Perú, but activist efforts that targeted these outcomes can inform women globally. The current study investigated key components of feminist activism by social movement actors themselves through the use of testimonio with nine key leaders in the movement. Using a liberation psychology approach and thematic narrative analysis, the findings suggested three key components of feminist activism: conflict, militant identity, and pluralism that were critical in processes of change. Centering majority world women’s voices contributes to the production of knowledge regarding approaches to gender equity, in particular because much that has been written about feminist action in psychology has been produced among white samples in the U.S. Implications for understanding how the findings have the potential for global change are discussed.